2021
DOI: 10.3390/app11146445
|View full text |Cite
|
Sign up to set email alerts
|

Production of Microfibrillated Cellulose from Fast-Growing Poplar and Olive Tree Pruning by Physical Pretreatment

Abstract: Motivated by the negative impact of fossil fuel consumption on the environment, the need arises to produce materials and energy from renewable sources. Cellulose, the main biopolymer on Earth, plays a key role in this context, serving as a platform for the development of biofuels, chemicals and novel materials. Among the latter, micro- and nanocellulose have been receiving increasing attention in the last few years. Their many attractive properties, i.e., thermal stability, high mechanical resistance, barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Olive tree pruning, made of a woody fraction (25%), leaves (25%), and thin branches (50%), is considered as one of the most abundant and inexpensive lignocellulosic residues produced in the Mediterranean countries (Contreras et al, 2020). Pulp and paper sheets (Dı áz et al, 2005), microfibrillated cellulose (Ibarra et al, 2021), and cellulose nanofibers (Fillat et al, 2018) were produced from olive tree pruning. Abdel-Halim et al (2015) converted cellulose extracted from olive tree pruning and having small length fibers and low mechanical strength into water-soluble hydroxypropyl carboxymethyl cellulose through two etherification reactions.…”
Section: Olive Tree Pruning Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Olive tree pruning, made of a woody fraction (25%), leaves (25%), and thin branches (50%), is considered as one of the most abundant and inexpensive lignocellulosic residues produced in the Mediterranean countries (Contreras et al, 2020). Pulp and paper sheets (Dı áz et al, 2005), microfibrillated cellulose (Ibarra et al, 2021), and cellulose nanofibers (Fillat et al, 2018) were produced from olive tree pruning. Abdel-Halim et al (2015) converted cellulose extracted from olive tree pruning and having small length fibers and low mechanical strength into water-soluble hydroxypropyl carboxymethyl cellulose through two etherification reactions.…”
Section: Olive Tree Pruning Biomassmentioning
confidence: 99%
“…Olive tree pruning, made of a woody fraction (25%), leaves (25%), and thin branches (50%), is considered as one of the most abundant and inexpensive lignocellulosic residues produced in the Mediterranean countries (Contreras et al., 2020). Pulp and paper sheets (Dı́az et al., 2005), microfibrillated cellulose (Ibarra et al., 2021), and cellulose nanofibers (Fillat et al., 2018) were produced from olive tree pruning. Abdel‐Halim et al.…”
Section: Olive Byproducts As Source Of Active Agentsmentioning
confidence: 99%
“…For example, for eucalypt, Fillat et al [ 21 ] found a reduction of 87.53% in DPv using TEMPO-ox reaction as a pretreatment. However, Ibarra et al [ 25 ] showed a reduction of 39% in DPv using physical pretreatment (PFI mill) prior to the microfluidization step. Normally, the decrease observed in this parameter is more pronounced in the case of TEMPO-ox reaction than in the physical pretreatments.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding nanofibrillation yield, poplar CNF showed a value of 87.3% ± 8.1%, indicating that almost all of the fibers in the starting material have been transformed to nano-sized. The nanofibrillation yield values for CNFs obtained by chemical TEMPO-ox pretreatment tend to be higher (80–100%) than those obtained when only physical processes are used (10–60%) [ 21 , 25 , 44 , 47 , 48 ]. This is due to the fact that sodium carboxylate groups are formed during the TEMPO-ox reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation